Planting density and variety intercropping improve organ biomass distribution of rapeseed to alleviate the trade‐off between yield and lodging resistance. Issue 4 (26th June 2021) - Wang, Zongkai; Wang, Bo; Kuai, Jie; Li, Zhen; Bai, Ru; Zhou, Guangsheng
Abstract: A split‐plot experiment was conducted to alleviate high yield and strong lodging resistance not coinciding with rapeseed ( Brassica napus L.). The main plot was planting density (1.2 and 4.5 × 10 5 plants ha −1 ), and the subplots were different intercropping ratios (1:0, 0:1, 2:1, 1:1, and 1:2) of Huayouza 62 (lodging resistance) and Fengyou 520 (lodging sensitive). Our results indicated that increased density significantly decreased biomass, siliques, and yield per plant, but the population yield was enhanced by 9.3%, and intercropping increased leaf area at the bolting and anthesis, dry matter accumulation, and population yield compared to the sole crop. Increased density decreased the root neck diameter and stem breaking strength of per plant but increased the population lodging resistance, and intercropping significantly improved lodging‐related agronomy traits, increased stem breaking strength, and stem biochemical contents compared to sole cropping. The average lodging index was decreased by 17.7% and lodging angle by 11.2% at the planting density of 1.2 × 10 5 plants ha −1 deployed at 1:2 intercropping ratio, and at 4.5 × 10 5 plants ha −1 with 1:1 intercropping ratio, the average lodging index decreased 7.8% and the lodging angle by 14.1%. Total population root biomass was significantly negatively correlated with the lodging angle, but positively correlated with the harvest yield. Intercropping rapeseed varieties that differ in lodging resistance at variable density can improve the root traits of the population that alleviate the trade‐off between high yield and poor lodging resistance. Core Ideas: Varieties intercropping significantly increased population seed yield. Varieties intercropping significantly improved lodging resistance in population. Intercropping can alleviate the trade‐off between high yield and poor lodging resistance.